BLINDNESS AND AUTISM SPECTRUM DISORDERS (Annual of the Faculty of Philosophy in Skopje, 2020)
Autism spectrum disorder (ASD) is common in children with blindness. Differentiatingbetween autistic-like features related to blindness and “true” autistic featurescan be very difficult, and demands clinical experience of children with blindnessand their typical development, as well as properly adapted assessment tools. The purposeof this study was to present an overview of the characteristics of blindness andASD. A literature review was performed according to PRISMA criteria. Publicationsfrom ERIC, EBSCO-Host, Science-Direct, PROQUEST, SCOPUS, and Google Scholarhave been analysed.Recent research has indicated that the prevalence of ASD may be higher in individualswith visual impairments (48%) than in the general population (1.5%), andthe risk of ASD increases with the severity of visual impairment. Also, research hasshown that certain aetiologies of blindness seem to have especially high comorbiditywith ASD, mainly optic nerve hypoplasia, retinopathy of prematurity, and anophthalmia.
Keywords: BLINDNESS; AUTISM SPECTRUM DISORDERS; PREVALENCE; INSTRUCTIONAL PROGRAMME